Predicting Daylight Illuminance for 15 CIE Standard Skies Using a Simple Software Tool - Tsang, Ernest Kin Wai; Li, Danny Hin Wa; Li, Shuyang (Frontiers in Sustainable Cities, 2022)
Estimation of internal daylight availability is the key step in evaluating various daylighting schemes. Traditionally, interior daylight is often expressed as daylight factor under overcast sky conditions. However, such approach may not be flexible enough to predict the dynamic variations as the sun’s position change under non-overcast skies. Recently, the International Commission on Illumination (CIE) adopted 15 standard skies covering the usual skies found in the world. The interior daylight illuminance is influenced by the sky conditions in terms of luminance levels and distributions in the direction of view of the window at any given time. The daylight coefficient concept which considers the changes in the luminance of the sky elements can be employed to accurately compute the indoor daylight level. A full-scale computer simulation can be costly in modelling the building geometry with a long simulation time. Moreover, additional times and advance skills are required for preparation and post-processing. Simple design programs would be convenient and useful during initial design stage when different designs and concepts are being studied and analyzed. This paper adopts a simple computer tool for determining the indoor daylight under the 15 CIE Standard skies. The performance of the proposed software was evaluated against the data simulated by a lighting program and the field-measurement readings.